2021
DOI: 10.3389/fphys.2021.611772
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria as a Biomarker for COVID-19 Severity

Abstract: BackgroundRenal involvement in syndrome coronavirus 2 (SARS-CoV-2) infection has been retrospectively described, especially acute kidney injury (AKI). However, quantitative proteinuria assessment and its implication in coronavirus disease 2019 (COVID-19) remain unknown.MethodsIn this prospective, multicenter study in France, we collected clinical and biological data including urinary protein to creatine ratio (UPCR) in patients presenting with moderate to severe COVID-19. Clinical outcome was analyzed accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 45 publications
(88 reference statements)
3
21
1
Order By: Relevance
“…Urinalysis and urine sediment examinations are the oldest and most commonly performed tests for assessing the pathophysiological condition of the kidney/urethral system. Urinalysis findings, such as proteinuria, hematuria, and leukocyturia, are reportedly associated with COVID-19-associated renal injuries and the severity of COVID-19 (Allemailem et al, 2021, Chan et al, 2020, Ouahmi et al, 2021, Pei et al, 2020, Yang et al, 2020, and several urinary chemical biomarkers, such as N-acetyl-β-D-glucosaminidase (NAG), α1-microglobulin (α1-MG), and neutrophil gelatinase-associated lipocalin (NGAL), have been proposed to be associated with AKI in hospitalized COVID-19 patients (Fukao et al, 2021, Huart et al, 2021, Husain-Syed et al, 2020, Luther et al, 2021. However, the characteristics of the urine sediment findings related to have not yet been studied adequately.…”
Section: Introductionmentioning
confidence: 99%
“…Urinalysis and urine sediment examinations are the oldest and most commonly performed tests for assessing the pathophysiological condition of the kidney/urethral system. Urinalysis findings, such as proteinuria, hematuria, and leukocyturia, are reportedly associated with COVID-19-associated renal injuries and the severity of COVID-19 (Allemailem et al, 2021, Chan et al, 2020, Ouahmi et al, 2021, Pei et al, 2020, Yang et al, 2020, and several urinary chemical biomarkers, such as N-acetyl-β-D-glucosaminidase (NAG), α1-microglobulin (α1-MG), and neutrophil gelatinase-associated lipocalin (NGAL), have been proposed to be associated with AKI in hospitalized COVID-19 patients (Fukao et al, 2021, Huart et al, 2021, Husain-Syed et al, 2020, Luther et al, 2021. However, the characteristics of the urine sediment findings related to have not yet been studied adequately.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that kidney involvement; particularly proteinuria is an important and independent predictor of outcome in SARS-CoV-2 infection [21,22,[25][26][27]. Ouahmi et al reported that proteinuria is related with increased length of stay and admission to intensive care unit (ICU) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that kidney involvement; particularly proteinuria is an important and independent predictor of outcome in SARS-CoV-2 infection [21,22,[25][26][27]. Ouahmi et al reported that proteinuria is related with increased length of stay and admission to intensive care unit (ICU) [21]. Chaudhri et al stated that proteinuria at admission was associated with AKI during hospitalization; and proteinuria during hospitalization was associated with increased risk of death [18].…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s kidney function was impaired during the acute progressive phase of COVID-19 with a markedly increased serum Cr level and decreased eGFR. Though his Cr level and eGFR eventually recovered to the normal level, the mechanism by which the SARS-CoV-2 virus impairs renal function remains unknown ( 16 , 17 ). Before his acute COVID-19 episode, he had never previously had detectable proteinuria in the 7-years since his living donor transplant.…”
Section: Discussionmentioning
confidence: 99%